Eptifibatide and 7E3, but not tirofiban, inhibit alpha(v)beta(3) integrin-mediated binding of smooth muscle cells to thrombospondin and prothrombin - Lele, M; Sajid, M; Wajih, N; Stouffer, G A (Circulation (New York, N.Y.), 2001)
Our objective was to determine whether abciximab, eptifibatide, or tirofiban inhibited ligand binding to alpha(v)beta(3) integrins on human aortic smooth muscle cells (HASMCs) or human umbilical vein endothelial cells (HUVECs). Abciximab binds alpha(IIb)beta(3) on platelets and alpha(v)beta(3) on HUVECs with similar affinity, whereas eptifibatide and tirofiban are thought to be highly specific for alpha(IIb)beta(3). The conclusion that eptifibatide does not bind vascular alpha(v)beta(3) integrins may be premature, however, because recent studies have demonstrated that the affinity of alpha(v)beta(3) for various ligands, including antagonists, is subject to modulation. Abciximab and 7E3, the anti-beta(3) integrin monoclonal antibody from which abciximab was derived, bound alpha(v)beta(3) on HASMCs in a specific and saturable manner and with an affinity similar to binding to alpha(IIb)beta(3) on platelets. 7E3 and eptifibatide inhibited alpha(v)beta(3)-mediated attachment of HASMCs to thrombospondin (TSP) and prothrombin but had no effect on alpha(v)beta(5)- or beta(1)-mediated HASMC attachment to vitronectin-, collagen-, or fibronectin-coated or noncoated tissue culture plates. The inhibitory effect of eptifibatide was similar in magnitude and not additive to that of 7E3. Eptifibatide and 7E3 inhibited alpha(v)beta(3)-mediated attachment of HUVECs. Tirofiban had only nonspecific effects on HASMC attachment to extracellular matrix proteins. In cell proliferation assays, eptifibatide inhibited alpha(v)beta(3)-mediated responses to soluble TSP by HASMCs and beta(3) integrin-expressing HEK cells. Eptifibatide and 7E3, but not tirofiban, specifically inhibit alpha(v)beta(3)-mediated binding of human smooth muscle and endothelial cells.